A COMPREHENSIVE 12-MONTH ANALYSIS: REAL-WORLD ASSESSMENT OF THE CARDIOVASCULAR RISK REDUCTION CLINIC (CRRC) AT HOSPITAL PULAU PINANG, MALAYSIA - MJ, Haseena Munawara; A, Zarina Banu; JW, Priscilia Foo; H, Nur Jawahi; J, Yeong; AA, Nurul Aishah; P, Rubendiran; AW, Mohamed Jahangir (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Atherosclerotic Cardiovascular Disease (ASCVD) remains the primary driver of cardiovascular disease (CVD)-related mortality, responsible for a staggering 80% of CVD-related deaths. The consistent association of low-density lipoprotein cholesterol (LDL-C) with CVD and coronary heart disease (CHD) underscores the potential of reducing LDL-C levels in mitigating atherosclerotic plaque progression and lowering ASCVD incidence. This has elevated lipidlowering therapies (LLT) as pivotal interventions to curtail ASCVD-related mortality and morbidity. METHODOLOGY This single-arm, observational study, enrolled patients aged 18 years and above with established ASCVD or ASCVDrisk equivalent conditions and LDL-C levels exceeding 1.8 mmol/L. RESULT A cohort of 58 patients, with a mean age of 57.5 (SD 11.0), predominantly male (86%), were included. Almost all patients had prior ASCVD (98.6%), 67.1% had a history of cardiac surgery/intervention and 71.4% had multivessel disease. Hypertension was common (74.3%), followed by diabetes (35.7%). Only 4.3% had familial hypercholesterolemia. Most patients were Malay (41.4%) and Chinese (38.6%). Fifty-seven (81.4%) had follow-ups at month 6 and thirty-four patients (48.6%) followed up at month 12. Analysis of patients who returned for follow-up showed that compared to baseline, mean LDL-C reduced by 1.7 mmol/L (44.0%) at month 6 (P <0.0001) and 1.20 mmol/L (38.3%) at month 12 (P <0.0001). However, none of the patients attained LDL-C <1.8 mmol/L and <1.4 mmol/L at baseline, 52.6% and 44.1% achieved LDL-C <1.8 mmol/L at month 6 (P <0.0001) and month 12 (P = 0.0003), respectively. Similarly, 26.3% and 20.6% attained <1.4 mmol/L at month 6 (P = 0.0003) and month 12 (P = 0.023) post-CRRC, respectively. CONCLUSION This pilot study provides substantial real-world evidence supporting the effectiveness of the Cardiovascular Risk Reduction Clinic in reducing mean LDL-C levels within 12 months. The findings underscore the positive influence of physician-prescribed lipid-lowering therapy strategies and patient counselling on LDL-C management.